Principles of Commentators and Jurisprudents in using Qaraat al-Mutawatara and Qaraat al-Shaza - Dr. Fareed Ud Din Tariq, (Al-Qanṭara, 2024)
The issue of Mutawatir (authentic) and Shadh (irregular) recitations has always been important in tafseer (interpretation) and fiqh (jurisprudence), as different forms of the Qur’anic recitation serve as a foundation for scholars when deriving legal rulings and interpretations. Mufassirun (interpreters) and fuqaha’ (jurists) consider various principles when accepting and benefiting from these recitations. Mutawatir recitations are those that have been transmitted with a continuous chain of narration such that the possibility of error or falsehood is eliminated. These recitations are considered an integral part of the Qur’an and are regarded as definitive by the Muslim community. Mufassirun and fuqaha’ regard Mutawatir recitations as conclusive evidence and fully utilize them for interpretation and deduction of rulings. These recitations are crucial for understanding the various meanings and implications of Qur’anic verses, and mufassirun use them as a foundation to clarify the meanings of different verses. Fuqaha’ derive legal rulings from Mutawatir recitations, as they are considered the authentic text of the Qur’an. Shadh recitations, on the other hand, are those that are not Mutawatir and have not been accepted by the majority, though part of their chain may be correct, and they often include narrations from some of the Sahabah (companions) and Tabi’un (followers). Mufassirun may use Shadh recitations as a supporting argument in tafseer, especially when these recitations help clarify the meaning of a verse or provide further explanation. However, Shadh recitations are not considered part of the Qur’anic text. Fuqaha’ do not directly derive legal rulings from Shadh recitations, though they may accept them as secondary or additional evidence in some cases. Mufassirun and fuqaha’ also find Shadh recitations useful for understanding the Arabic language and its literary and linguistic principles. If a Shadh recitation does not contradict the fundamental message and rulings of the Qur’an, mufassirun and fuqaha’ can benefit from it. Such recitations that strengthen the linguistic or literary aspects or clarify a specific meaning can be utilized in tafseer. Some mufassirun accept Shadh recitations when they have been reliably transmitted from the Sahabah or Tabi’un, even if they do not reach the level of Mutawatir. There is disagreement among mufassirun regarding how much benefit can be derived from Shadh recitations in tafseer. Some mufassirun reject them, while others give them importance in interpretation. Fuqaha’ generally regard Mutawatir recitations as the primary source for deriving legal rulings, although some fuqaha’ may accept Shadh recitations as evidence in specific circumstances. In summary, Mutawatir recitations hold definitive status among mufassirun and fuqaha’, and they rely on them for tafseer and fiqh. Shadh recitations are often used as supporting evidence in tafseer, but caution is exercised when deriving legal rulings from them.